2014
DOI: 10.3928/1081597x-20140903-03
|View full text |Cite
|
Sign up to set email alerts
|

Additive Effect of Repeated Corneal Collagen Cross-linking in Keratoconus

Abstract: PURPOSE: To report the long-term clinical outcome in a patient diagnosed as having bilateral progressive keratoconus who received a single corneal collagen cross-linking (CXL) treatment in the right eye and repeated CXL in the left eye. METHODS: Observational case report. Topographical changes were assessed by high-resolution Scheimpflug imaging. The right eye underwent a standard epithelium-off CXL procedure in February 2008, followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 10 publications
0
10
0
1
Order By: Relevance
“…In an adult patient, retreatment resulted in further 4 D of flattening in Kmax over a period of 2 years. 105 In a recently published series of 62 eyes of pediatric patients, two children showed progression up to 3.2 D in Kmax by the 36-month follow up visit, requiring retreatment. Both patients experienced stabilization of Kmax values 12 months after retreatment.…”
Section: Outcomes Of Pediatric Cross-linkingmentioning
confidence: 97%
“…In an adult patient, retreatment resulted in further 4 D of flattening in Kmax over a period of 2 years. 105 In a recently published series of 62 eyes of pediatric patients, two children showed progression up to 3.2 D in Kmax by the 36-month follow up visit, requiring retreatment. Both patients experienced stabilization of Kmax values 12 months after retreatment.…”
Section: Outcomes Of Pediatric Cross-linkingmentioning
confidence: 97%
“…The results obtained are further encouraging in light of the evidence that inadequate cross-linking effect can be augmented by further treatment. 24 Thus, it becomes increasingly important to produce a cross-linking treatment characterized by minimal risk and maximal compliance.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, failure and progression of keratectasia after primary CXL have also been reported [7,8]. Although the definition and criteria of progression after CXL has been reported [9], a series of studies [10][11][12][13] revealed diverse signs of deterioration after CXL, including tomographic progression, worse ocular refractive status, and even morphological alteration observed by anterior segment optical coherence tomography or in vivo confocal microscopy. Whether repeated CXL should be performed to manage keratoconus progression needs more elucidation.…”
Section: Introductionmentioning
confidence: 99%